Measurement of amniotic fluid by ultrasonography. - Pacheco, José (2015)
The amount of amniotic fluid is studied by measuring wells in millimeters high by ultrasonography in 300 normal pregnant women who were enrolled in different stages of pregnancy without complications, date of last normal menstruation precisada well, with only normal fetal development, no major malformations or delay growth and macrosomia, with apparently normal placentas without premature ripening. The well height during pregnancy ranged from an average of 32.5 mm. between 11 and 12 weeks to 61.3 mm. between 28 and 32 weeks, then remain more or less stationary values to 40 weeks. The maximum and minimum limits in the second half of pregnancy were 80 and 40 mm., Which corroborates in our results reported in other countries.